Avaliação do conhecimento em odontologia e educação física acerca dos protetores bucais - SIZO, Sérgio Rodrigues (Universidade Federal do Pará, 2017)
This study had the aim to assess the level of knowledge of 150 Odontology and Physical Education undergraduation students concerning mouth guards in the city of Belém, Brazil. Besides that, we tried to provide further information to these future professionals through speeches and distribution of folders in which the main focus was the mouth guards, their indications, types as well as hygienization and storage. The participants in the research were in the last year of their specific undergraduation courses. The analysis of the results showed that 68% of the interviewed students still do not have suitable information on the mouth guards, but despite of that, in their majority they are aware of the risks many athletes face in sports which have physical impact. The authors believe the spread of the information on the use of mouth guards in sportive practice is relevant and aims to prevent trauma and promote health of general population.